2002
DOI: 10.1542/peds.109.1.e5
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the Association Between Age of First Sexual Intercourse and Subsequent Human Papillomavirus Infection

Abstract: ABSTRACT.Objective. Previous studies have demonstrated that early age of first sexual intercourse is associated with human papillomavirus (HPV) infection. The objective of this study was to identify a set of risk behaviors and partner characteristics that mediate the association between age of first sexual intercourse and subsequent HPV infection in adolescent and young adult women.Methods. Female university students completed surveys and underwent HPV testing every 6 months for up to 3 years. HPV-positive par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 46 publications
7
70
1
8
Order By: Relevance
“…This additional restriction allowed a more precise examination of the role of the male factor in the acquisition of infection. 9,10 We found that older partners were more likely to be reported as sexually experienced and that among women with sexually experienced partners, the risk of infection increased with increasing age of partner.…”
Section: Discussionmentioning
confidence: 79%
“…This additional restriction allowed a more precise examination of the role of the male factor in the acquisition of infection. 9,10 We found that older partners were more likely to be reported as sexually experienced and that among women with sexually experienced partners, the risk of infection increased with increasing age of partner.…”
Section: Discussionmentioning
confidence: 79%
“…The age at first sexual intercourse, time since first sexual intercourse, use of oral contraceptives, and a smoking habit revealed an association with HPV infection in a crude analysis but not in a multivariate analysis. Across various studies, the results of the association between these variables and HPV infection have been inconsistent (15,21,23,24). A possible explanation may be that they could be a marker for other risky sexual behavior (e.g., greater numbers of partners; ref.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be that they could be a marker for other risky sexual behavior (e.g., greater numbers of partners; ref. 24).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, é necessário ajustar este dado para a idade do início da atividade sexual, sendo estes dois fatores muito importantes em relação ao risco de infecção por HPV (KAHN et al, 2002a). Assim, quanto mais precoce o início das atividades sexuais, maior o risco de infecção (KAHN et al, 2002b). Na idade de 50 anos, 80% das mulheres terão sido contaminadas por esse vírus (BROOMALL; REYNOLDS; JOCOBSON, 2010).…”
Section: Resultsunclassified